Influence Of Low Concentration Diamond-Water Nanofluid On Heat Transfer In Loop Heat Pipe - Tan, Siew Aun (2018)
An experimental works were conducted to investigate the heat transfer characteristics by using low concentrations of diamond-water, which was less than 1% in Loop Heat Pipe (LHP) in this thesis. The nanofluid consists of three types of mass concentration which is 0.3%, 0.6% and 0.9%. This study on LHP with low concentration of nanofluid were divided into three condition changes for the entire of study, which was flow rate changes, different heat load applied and different working fluid. For the effect of working fluid flow rate, the optimum flow rate to gain the lowest total thermal resistance of LHP was 7.5ml /min from the setting of 5ml /min to 10ml /min. The evaporator heat transfer coefficient also observes increase 16.7% for 0.9% diamond-water than pure water at flow rate 7.5m l /min. In term of influence of heat load to LHP, higher heat load 60W provides lower total thermal resistance of LHP. Same goes to heat transfer coefficient improve about 10.95% for mass concentration 0.9% diamond-water compared with water. On the effect of different nanofluid towards total thermal resistance, a comparison study between silica-water and diamond-water at mass concentration of 0.6% would be covered in the present experiment. Nevertheless, the diamond-water nanofluid has lower total thermal resistance of LHP than silica-water nanofluid. In the mean time, the experimental results were compared with ANSYS simulation and both were found to be in good agreement. Thus, there is a potential for low concentration of diamondwater nanofluid to be utilized as working fluid, in terms of high thermal conductivity.